30 trees and why landscape architects love them - Henderson, Ron, 1961- (Basel, Switzerland Birkhäuser, 2024)
30 Trees presents the favorite trees of 30 internationally renowned landscape architects. In each case, the designers describe the characteristics that represent the essence of the selected tree, the designed landscapes they associate with it, and how it was used in completed projects. These personal insights are complemented by five scholarly essays on criteria such as typology, ecology, maintenance, and seasons that are critical in matching trees to landscapes. Additionally, the book includes a botanical description of each species mentioned. The result is a compendium of insights into tree species and the use of trees in landscape architecture.--Back cover.
Includes tree index
Includes bibliographical references.
Keywords: Trees; Ornamental trees; Landscape architecture; Landscape gardening; Arbres; Trees (woody plants)